In-situ fabrication of amorphous/eutectic Al2O3–YAG ceramic composite coating via atmospheric plasma spraying. Issue 16 (December 2016) - Yang, Kai; Rong, Jian; Feng, Jingwei; Zhuang, Yin; Tao, Shunyan; Ding, Chuanxian
Abstract: The microstructure and property of plasma-sprayed Al2 O3 –Y3 Al5 O12 (YAG) composite coatings were investigated. The sprayable feedstock was composed of Al2 O3 /Y2 O3 granules obtained from the spray drying. As-sprayed Al2 O3 –YAG composite coating showed obvious amorphous characteristics. Post-heat treatment facilitated the complete crystallization of the Al2 O3 –YAG composite coating. The heat-treated Al2 O3 –YAG ceramic coating possessed the deposition microstructure comprising three-dimensional interpenetrating network of α-Al2 O3 /YAG eutectic phases, which is very similar to the directional solidification microstructure of Al2 O3 /YAG eutectic bulk ceramics. This eutectic coating microstructure does not correspond to a traditional eutectic microstructure. Al2 O3 –YAG ceramic coating with eutectic composition is obtained from the crystallization of an amorphous solid ceramic instead of the solidification of the liquid. Furthermore, the plasma-sprayed Al2 O3 –YAG eutectic ceramic coating with the heat treatment exhibits excellent microstructure and performance stabilities under high temperature.